Policía Comunitaria y Efectividad Policial en El Salvador - Editor, El (Revista Policía y Seguridad Pública, 2014)
DOI: http://dx.doi.org/10.5377/rpsp.v1i1.1397 Revista Policía y Seguridad Pública 1(1) 2012: 359-364